Challenging hegemony? : a provincial perspective on the limits of policy challenge in the South African state - Reynolds, John (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
This thesis provides a provincial perspective on the limits of policy challenge within the post-apartheid South African state. This perspective is located in the Eastern Cape Province of South Africa, which is one of the poorest of the nine provinces into which the national territory was divided during the constitutional negotiations prior to the landmark democratic elections of 1994. The empirical foundation for this perspective is an analysis of the process of developing the Eastern Cape Provincial Growth and Development Plan 2004-2014 (PGDP), which took place in 2002-2004. Starting with a broader theoretical discussion, followed by a brief contextual analysis of the South African economy, the structure of the post-apartheid South African state, and key growth and development policies, the more detailed engagement with the PGDP process is undertaken. Drawing on Jessop's (2008) strategic-relational approach, this thesis argues that the PGDP process arose within a particular spatio-temporal context where new opportunities for policy challenge were possible, but that such challenge had to be negotiated on a strategically selective terrain on which that challenge was neutralised. The PGDP process unfolded as a complex dialectic of agency and a range of path-dependent institutional processes with varying temporal and spatial horizons (cf. Pierson, 2004, 2005) in which no particular outcomes were guaranteed, but in terms of which some outcomes were more likely than others. Although the organisation of state power was expressed in the content of the PGDP, that power had to be understood as fractured across a range of state and non-state institutions, but with the state as the primary site of the contingent organisation of power. The provincial sphere of government faces particular constraints with the South African state, which has implications for its policy scope and the possibilities of policy challenge, even where wider social support is achieved.
Keywords: Community development -- South Africa -- Eastern Cape; South Africa -- Politics and government -- 1994-